MANUFACTURE OF NATURAL HUMAN-HAIR FIBER-REINFORCED COMPOSITES WITH COMBINED 0°/±45° FIBER ORIENTATION - Okta Pianti Rahayu; Antonius Adi Soetopo; Marta Hayu Raras Sita Rukmika Sari (Politeknik META Industri Cikarang, 2026)
Background Human hair is an abundant biodegradable waste material generated worldwide; however, its potential as a reinforcement material in polymer composites remains largely underutilized despite its favorable tensile properties compared with many natural fibers. Existing studies have primarily focused on simple fiber orientations, while the mechanical performance and reliability of human-hair composites with combined fiber orientations have received limited attention Purpose This study aims to evaluate the tensile and flexural properties of a human-hair fiber- reinforced epoxy composite with a combined 0°/±45° symmetric and balanced fiber orientation and to assess the reliability of its mechanical performance using Weibull statistical analysis Methodology Human hair fibers were chemically treated with a 5% NaOH solution for 30 minutes and reinforced with an Epoxy Bakelite EPR-174 matrix at a 50:50 fiber-to-matrix weight ratio using the hand lay-up fabrication method. The composite specimens were cured at room temperature for 12 hours and tested according to ASTM D3039 for tensile properties and ASTM D7264 for flexural properties. A Weibull distribution analysis was performed to evaluate the reliability of the measured mechanical properties. Findings The developed composite exhibited an average tensile strength of 32.24 MPa and an average flexural strength of 63.13 MPa. Based on Weibull analysis, the predicted strengths at 90% reliability were 31.05 MPa for tensile loading and 60.00 MPa for flexural loading. The combined 0°/±45° fiber orientation effectively distributed the applied load across multiple fiber directions, resulting in lower tensile strength than a fully unidirectional 0° laminate while providing a more balanced mechanical response and enhanced structural reliability. Implications The findings demonstrate that human-hair fiber composites have significant potential as sustainable and environmentally friendly reinforcement materials for lightweight composite applications. Future studies should investigate additional fiber orientations, optimize fiber volume fractions, and incorporate density characterization following ASTM D792, together with microstructural analyses, to further improve mechanical performance and validate failure mechanisms. Originality This study is the first to provide a reliability-based mechanical characterization of a human-hair fiber-reinforced Epoxy Bakelite EPR-174 composite with a combined 0°/±45° symmetric and balanced fiber orientation. The integration of experimental mechanical testing and Weibull reliability analysis offers new insights into the structural performance of biodegradable hair fiber composites for engineering applications.